The Impact of Human Faces on Social Media Engagement: A Comparative Study of Premium and Economy Automobile Brands Across Multiple Platforms - Merta, Franz (2025)
Social media is a central channel for automobile communication, and it has profoundly changed how brands interact with their audiences. Although prior literature has already established that human faces can have a positive impact on engagement in industries like fashion and technology, the effectiveness of this feature in product-centric industries, like the automotive industry, seems to be mostly unexplored. This thesis attempts to answer four relevant research questions on how the presence and characteristics of human faces in social media posts influence user engagement, measured by likes, comments, shares, and total interactions, across Facebook, Instagram, and X (formerly Twitter), for both premium and economy automotive brands. By reflecting on theories of platform-specific engagement patterns, face perception, and anthropomorphism, this thesis analysed 1,800 social media posts from six top-performing global automotive brands using non-parametric statistical methods. It compares engagement metrics based on the presence of faces, gender representation, platform, and brand position. Contrary to expectations seen in other industries, the findings reveal that posts without human faces generally received higher engagement, especially on Facebook and X, and among premium brands. Nonetheless, the detailed analysis shows that posts featuring human faces may perform better for economy brands and can create stronger engagement on visually oriented platforms like Instagram. Additionally, posts featuring female faces consistently received higher engagement rates across the data, suggesting a strong difference in impact between genders. These results support the view that human imagery does not always improve engagement in social media communication and validates the importance of tailoring content to platform- and position-specific environments. This thesis also offers managerial implications for industry practitioners and contributes to the academic literature on content effectiveness, face perception, and platform-specific social media strategies.